2020
DOI: 10.1002/hed.26244
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between host transcriptome‐derived HPV oncogene E6* influence score and carcinogenic pathways, tumor size, and survival in head and neck cancer

Abstract: Background Human papillomavirus (HPV) oncogenes E6, E7, and shorter isoforms of E6 (E6*) are known carcinogenic factors in head and neck squamous cell carcinoma (HNSCC). Little is known regarding E6* functions. Methods We analyzed RNA‐seq data from 68 HNSCC HPV type 16‐positive tumors to determine host genes and pathways associated with E6+E7 expression (E6E7) or the percent of full‐length E6 (E6%FL). Influence scores of E6E7 and E6%FL were used to test for associations with clinical variables. Results For E6E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…E1 was the HPV gene most frequently involved in integration (40% of sites), which is in agreement with previous studies. 12,41 Even though there were a limited number of integration sites detected (n = 35), we were able to determine that integration events took place across 11 different chromosomes (chromosomes 1,2,3,4,6,7,8,9,13,14,17). Of the integration sites detected, only eight (23%) were within cellular genes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…E1 was the HPV gene most frequently involved in integration (40% of sites), which is in agreement with previous studies. 12,41 Even though there were a limited number of integration sites detected (n = 35), we were able to determine that integration events took place across 11 different chromosomes (chromosomes 1,2,3,4,6,7,8,9,13,14,17). Of the integration sites detected, only eight (23%) were within cellular genes.…”
Section: Discussionmentioning
confidence: 94%
“…We assessed the expression of alternate E6* transcripts; these transcripts are thought to contribute to a more aggressive phenotype, resulting in larger tumors and worse patient prognosis 17 . We found that the majority of samples expressed both E6FLE7 and alternate E6* transcripts with a few samples only expressing E6* transcripts.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, the enriched signaling cascade for the 359 upregulated and 366 downregulated genes identified by the analysis of the KEGG pathway was selected according to log 2 FC (p < 0.05). In the high-risk subgroup, the top-ranking terms were associated with "ribosome, " "oxidative phosphorylation, " "non-alcoholic fatty liver disease, " and "synaptic vesicle cycle, " and so on (p < 0.05); among them, "oxidative phosphorylation" was testified to be related to larger tumor size of HNSCC (Figure 8G) (42). Verification of the low-risk subgroup with KEGG analysis also revealed that "cell cycle" and "HTLV-infection" were linked with these genes (Figure 8H).…”
Section: Functional Annotation and Pathways Of Two Risk Subgroups Determined By Three Prognostic Genesmentioning
confidence: 99%